Brucellosis: An Unrecognized Zoonotic Disease in Indonesia - Noor, Susan Maphilindawati (Indonesian Animal Sciences Society, 2006)
Brucellosis, a bacterial zoonosis, is a disease caused by members of the genus Brucella . In Indonesia, brucellosis has known as a contagious reproductive disease in animals, however, only certain people know that brucellosis can be transmitted to human . Bovine brucellosis is characterised by one or more of the following signs : abortion, retained placenta . orchitis, epididymitis and, rarely, arthritis, with excretion of the organisms in uterine discharges and in milk . The Brucella organism is transmitted to human most commonly by ingestion of untreated milk or milk products or through the mucous membranes and wound of the skin . The severity of human disease varies, depending largely upon the infecting strain . Brucella abortus, B . melitensis. B . suis and B. canis are highly pathogenic for humans . Clinical symptoms of human brucellosis may include an intermittent fever, headaches, weakness, arthalgia, myalgia and weight loss . Occasional complications include arthritis, endocarditis, hepatitis granuloma, meningitis, orchitis dan osteomyelitis have also been reported . Brucellosis can also produce spontaneous abortion in pregnant woman . Diagnosis is based on the isolation of the organism and serology . Antibiotics are usually the mainstay of treatment and long-term treatment may be required . Brucellosis can be controlled by comprehensive campaigns to eradicate the disease by vaccination programme followed by test and slaughter of domestic animals which exhibit positive serologic reactions to brucellae. Â Key words : Brucellosis, zoonosis, diagnose, control